The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/432164
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Function following Partial Calcanectomy in High-Risk Limb Salvage Patients

Abstract: Partial calcanectomy (PC) is an established limb salvage procedure for treatment of deep heel ulceration with concomitant calcaneal osteomyelitis. The purpose of this study is to determine if a relationship exists between the amount of calcaneus removed during PC and the resulting lower extremity function and limb salvage outcomes. Consecutive PC patients were retrospectively divided into two cohorts defined by the amount of calcaneus resected before wound closure: patients in cohort 1 retained = 50% of calcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the study by Oliver et al (2015), 42 patients with calcaneal osteomyelitis and partial calcanectomy were included 11. The patients were divided into two cohorts with a resection of the calcaneum of <50% and >50%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Oliver et al (2015), 42 patients with calcaneal osteomyelitis and partial calcanectomy were included 11. The patients were divided into two cohorts with a resection of the calcaneum of <50% and >50%.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies described treatment in a single stage 9,10,13,14,16,18,21,23,24. Only 2 papers describe 2 stage procedures 11,20. In both papers, skin closure was performed separately after the first stage bone excision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite difficulties in obtaining a successful conservative treatment, several clinical studies have recently shown the possibility of the limb salvage procedure. 12-14 Partial calcanectomy surgical procedure was described for the first time in 1896. 15 Over the past 25 years, several articles were published describing this procedure as a salvage treatment.…”
mentioning
confidence: 99%
“…with large heel ulcers and calcaneus OM. 8) In fact, it has also been reported that proper revascularization and PC are effective. 9) We could minimize the deterioration of our patient s quality of life by treating her with PC and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%